Bounding Pyramids and Bounding Cones for Triangular Bézier Surfaces (Journal of Computational Mathematics, 2021)
This paper describes practical approaches on how to construct bounding pyramids and bounding cones for triangular Bézier surfaces. Examples are provided to illustrate the process of construction and comparison is made between various surface bounding volumes. Furthermore, as a starting point for the construction, we provide a way to compute hodographs of triangular Bézier surfaces and improve the algorithm for computing the bounding cone of a set of vectors.